Rancang Bangun Alat Kontrol dan Monitoring Konsumsi Listrik Lampu Penerangan Jalan Umum Berbasis Mikrokontroler ATMega 2560 - Anggara, Surya Puja; Amrita, A.A Ngurah; Khrisne, Duman Care (Majalah Ilmiah Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i03.P18, 2018)
Abstract — Public street lighting (LPJU) is a road infrastructure that is very important for road users at night. The constraints faced by User managers in an area in LPJU management are the problem of maintenance, monitoring, electricity consumption, and limited workforce. In an effort to overcome this problem, this study designed a tool in the LPJU system that can control LPJU ignition according to user needs by combining the timer and light sensor functions, and can monitor electricity consumption by calculating the power consumption or kWh meter and recording data on accumulation of electric power consumption every day at 06.00 WITA automatically stored on the micro SD Card. The accumulated data last recorded for 1 (one) month at the beginning of each month at 08.00 WITA will be sent using SMS services to users periodically. In addition, the user can monitor at any time with the " lapor " SMS format, the monitoring data sent in the form of the last electrical power consumption used by LPJU at that time.